2012
DOI: 10.1039/c1ob06278f
|View full text |Cite
|
Sign up to set email alerts
|

Solid state NMR studies of oligourea foldamers: Interaction of 15N-labelled amphiphilic helices with oriented lipid membranes

Abstract: Synthetic oligomers that are derived from natural polypeptide sequences, albeit with unnatural building blocks, have attracted considerable interest in mimicking bioactive peptides and proteins. Many of those compounds adopt stable folds in aqueous environments that resemble protein structural elements. Here we have chemically prepared aliphatic oligoureas and labeled them at selected positions with (15)N for structural investigations using solid-state NMR spectroscopy. In the first step, the main tensor eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…This permitted to acquire information on the oligomers’ conformation, dynamics, and interactions with model membranes. The acquired data were indicative of an alignment of the oligourea helix parallel to the surface of the phospholipid bilayers, in agreement with the amphipathic character of the foldamer and consistent with previous models explaining the modes of action of AMPs (Aisenbrey et al, 2012). …”
Section: The Raise Of Peptide Mimeticssupporting
confidence: 90%
See 1 more Smart Citation
“…This permitted to acquire information on the oligomers’ conformation, dynamics, and interactions with model membranes. The acquired data were indicative of an alignment of the oligourea helix parallel to the surface of the phospholipid bilayers, in agreement with the amphipathic character of the foldamer and consistent with previous models explaining the modes of action of AMPs (Aisenbrey et al, 2012). …”
Section: The Raise Of Peptide Mimeticssupporting
confidence: 90%
“…High resistant to proteolytic degradation oligoureas have been shown to adopt a remarkably stable helical fold stabilized by 12- and 14-membered H-bonded rings, with helical propensity being enhanced in the presence of phospholipid vesicles, and to possess significant antibacterial activity against Gram-negative and Gram-positive bacteria (Violette et al, 2006; Claudon et al, 2010). Recently, a detailed solid-state NMR structural investigation was performed on aliphatic oligoureas synthesized with 15 N at selected positions (Aisenbrey et al, 2012). This permitted to acquire information on the oligomers’ conformation, dynamics, and interactions with model membranes.…”
Section: The Raise Of Peptide Mimeticsmentioning
confidence: 99%
“…[34] This finding is in agreement with previous studies, [35] in particular with work by Bechinger and co-workers, who used solid-state NMR spectroscopy to observe helix formation and orientation of some AMPs upon contact with lipid bilayers. [36] Other biophysical studies confirmed differential interaction of amphipathic AMPs with zwitterionic versus anionic lipids. [37] Using deep-UV Raman spectroscopy Cooley and co-workers provided the first evidence of lipid-dependent secondary structure (helix) formation and aggregation of ME1 peptide in the presence of micelles.…”
mentioning
confidence: 85%
“…Solid state nuclear magnetic resonance (ss-NMR (19)) is a powerful analytical technique that can determine structures in non-dissolved systems with quasi-atomic resolution. It can be used to characterize membrane-bound structures (20,21), and it can yield detailed information on the conformation and dynamics of membrane-bound proteins and peptides (22,23,24) and their artificial mimics (25). It has recently been used to investigate both the structure and dynamics of the photoswitchable vision protein rhodopsin (26), and provides evidence that the solution-phase conformational preference of the Aib-rich peptaibol alamethicin is preserved when embedded in phospholipid bilayers (27).…”
mentioning
confidence: 99%